The Decision of Married Woman to Inspect IVA Test in Deli Serdang, Indonesia - Nurbaity; Zulfendri; R. Kintoko Rochadi (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to find out the decision of married woman to inspect IVA Test in Deli Serdang, Indonesia. This type of research is an analytical survey research with cross sectional approach (Arikunto, 2010), which aims to determine the relationship of power relations with the low coverage of IVA Test coverage. The result shows that the dominance of power in the household, socio-economic that has a relationship with the decision making to conduct an IVA test in Deli Serdang Regency, It can be concluded several things.